EFEKTIVITAS MODEL PROBLEM BASED LEARNING BERMEDIAKAN LEMBAR KERJA PESERTA DIDIK TERHADAP HASIL BELAJAR KIMIADAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK SMA - RAMLAN SILABAN; FREDDY TUA MUSA PANGGABEAN; ESRIDA HUTAHAEAN; FELIA MUTIARA HUTAPEA; IRVING JOSAFAT ALEXANDER (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2021)
The aim of this research is to know the effectivenessproblem based learning model (PBL) using student worksheet on learning outcomes and students’critical thinking skills on the teaching Reaction Rate. The population in this research was grade 11th of SMA Negeri 6 Medan. Classes sample was taken by random sampling, and two classes were selected as a sample. Those two classes will be taught with Problem Based Learning model, the difference is the first class will be used students worksheets and the other class is not. The instrumentto conduct this researchwas by test and non-test. Based on parametric statistical test, the result of pretest, postest, and students’ critical thinking skills data from those two classes have a normal distribution and homogeny. Hypothesis was tested by using one tailed test with significant level ( ) =0,05. The data from hypothesis testing learning outcomes is tcal ttable (3,101 1,669), means Hois rejected and Ha is accepted. Hypothesis testing result on students’ learning outcomes using student worksheets is higher than the non-using student worksheet. Critical thinking hypothesis test is tcal ttable (4,754 1,669), means Hois rejected and Ha is accepted. Hypothesis testing result oncritical thinking using student worksheet is higher than the non-using student worksheet. Contribution of students’ critical thinking to the ups and downs of learning outcomes on the experiment class is 81,5%.